Mentoring for gender equality: Supporting female leaders in the hospitality industry. (July 2020) - Dashper, Katherine
Highlights: Hospitality organisations and careers are built around an invisible masculine norm. Women experience gendered barriers to progression. Mentoring is a useful function to support women's career development. Mentoring can help challenge persistent gender inequality. Abstract: The hospitality industry struggles with problems with staff motivation, commitment and retention, whilst also having an entrenched glass ceiling that limits career opportunities for many women. Mentoring is a useful function to support and develop staff, and may be particularly important for helping women overcome gendered barriers to progression. This paper reports on a year-long qualitative study of a women's mentoring programme in the hospitality industry in the UK. Drawing on data from 71 interviews with a sample of 13 mentors and 14 mentees, the findings illustrate the persistent gendered obstacles women experience as they try and negotiate careers in masculinist hospitality organisations. The mentoring programme offers individual support for the mentees, and also begins to challenge gendered discourses of success in hospitality careers, illustrating that mentoring has an important role to play in both career development and in confronting gender inequality in the hospitality industry.